A description of Gorenstein projective modules over the tensor products of algebras. Issue 7 (3rd July 2019) - Shen, Dawei
Abstract: Let A be a two-sided coherent algebra over a field k and B be a finite-dimensional algebra. If B is Gorenstein, we give a description of finitely presented Gorenstein projective modules over the tensor product of A and B in terms of their underlying modules over A and B . If B has finite global dimension, we also give another description.